1998
DOI: 10.1046/j.1365-2249.1998.00728.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic experimental colitis induced by dextran sulphate sodium (DSS) is characterized by Th1 and Th2 cytokines

Abstract: SUMMARYOral administration of DSS has been reported to induce an acute and chronic colitis in mice. The aim of our study was to evaluate if the chronic phase of DSS-induced colitis was characterized by a Th1/Th2 response and how this would relate to mucosal regeneration. Swiss Webster mice were fed 5% DSS in their drinking water for 7 days, followed by 2-5 weeks consumption of water. Control mice received only water. The animals were killed at 3 and 6 weeks after induction. Their colons were isolated for histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
735
1
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 961 publications
(775 citation statements)
references
References 32 publications
25
735
1
1
Order By: Relevance
“…In addition, inhibition of endogenous IFN g by antibodies has been shown to ameliorate the chronic stage of colitis, indicating that IFN g is likely a key mediator for intestinal inflammation. 28 Here, we demonstrated that IFN g increases CD98 glycoprotein expression in Caco2-BBE monolayers. This observation is consistent with the CD98 upregula- …”
Section: Discussionmentioning
confidence: 61%
“…In addition, inhibition of endogenous IFN g by antibodies has been shown to ameliorate the chronic stage of colitis, indicating that IFN g is likely a key mediator for intestinal inflammation. 28 Here, we demonstrated that IFN g increases CD98 glycoprotein expression in Caco2-BBE monolayers. This observation is consistent with the CD98 upregula- …”
Section: Discussionmentioning
confidence: 61%
“…WT mice showed a weak, polarized Th1 response during the acute disease phase and a mixed Th1/Th2 response during the chronic phase of the inflammation, as described [32,37]. In contrast, CCR6-deficient mice did not show a specific Th1 response, as basal IFN-+ mRNA levels in colon, which are about twofold higher than those of WT mice, did not increase in either the acute or the chronic phase of DSS-induced colitis.…”
Section: Discussionmentioning
confidence: 78%
“…Induction and evaluation of DSS-induced colitis were performed according to the previous reports [26][27][28]45,46 with some modifications. In brief, mice were given 2% DSS (molecular weight 36,000-50,000; ICN Biomedicals, Burlington, ON, Canada) dissolved in sterile distilled water for 7 days.…”
Section: Methodsmentioning
confidence: 99%